On the Good News in Equity Carve-Outs - Nanda, Vikram (Journal of Finance, 1991)
The announcement of the sale of equity in a wholly owned subsidiary of a corporation is received by the market as good news about the value of the existing equity in the parent corporation. This is in stark contrast to announcements of other forms of public equity financing. We show that the apparent inconsistency between the market response to equity carve-out announcements and other forms of equity financing can be easily understood in the Myers and Majluf (1984) framework. It is shown that firms that resort to an equity carve-out will be firms that, on average, are being undervalued by the market.